Exploring the Link Between Ativyayama (Overexercise) and Srotodusti, with Emphasis on Pranavaha Srotas: A Comprehensive Scientific Analysis - Surekha Kamath; Rashmi Bairwa; Srinidhi Shetty; Prabhjot Kaur; Balakrishan Sevatkar (AYUSHDHARA, 2024)
Vyayama, a specialized concept in Ayurveda, serves as both the cause and remedy for various illnesses. While physical exercise is beneficial, excessive engagement in it can lead to negative health outcomes. Over-exertion aggravates the Vata Dosha, which in turn affects the qualities of the channels (Srotas), making them Ruksha and Khara. Consequently, Vyayama becomes a primary factor in the disturbance of the channels Pranavaha, Asthivaha, and Swedavaha Srotas. Conversely, insufficient exercise disrupts the Medovaha Srotas. The Pranavaha Srotas serves as the vital channel responsible for carrying Vata, especially Prana, which sustains the vitality of every cell. Disruption in the structure or function of this channel leads to illness. When exercise is excessive, it can lead to Hridayoparodha resulting in impairment of the primary site of action. This can manifest as acute conditions (as myocardial infarction) or chronic conditions (as Shosha). It’s important to engage in exercise appropriately according to Bala and Ritu to preserve health. This article explores the scientific evidence supporting the notion that excessive exercise (Ativyayama) can disturb the balance of the body’s channels, particularly the Pranavaha Srotas. It offers a thorough examination of the relationship between overexercise and channel disturbances, providing insights into potential risks and preventive measures.